Digitalization of Marketing to Support MSMEs in the Midst of the Covid-19 Pandemic - Nasution, Winda Suci Lestari (Talenta Publisher, 2022)
Digitalization Technology is currently growing and the benefits of using the internet are felt for its users. Some people feel dependent on the internet, including the activities of Micro, Small and Medium Enterprises (SMEs) in utilizing digitalization to run their business, especially for MSMEs. The purpose of this community service is to open an alternative discourse on the marketing process of existing micro, small and medium enterprises (MSMEs) products through digital media-based marketing efforts and maximize network-based communication-based marketing efforts that lead to increased marketing of these MSME products. This is an important factor considering that conventional marketing activities are hampered due to the spread of Covid-19 and because marketing through digital media has become a very broad opportunity as an alternative solution that can be offered on the one hand, and on the other hand, the use of digital media as a marketing tool is also necessary. get a high portion of attention from the government and other stakeholders to facilitate, educate and maintain and improve the marketing activities of MSME products.